Cardiac Organ Damage in Young Adults with Cryptogenic Ischaemic Stroke: The SECRETO Study - Eilertsen, Rune Krogh; Gerdts, Eva; Waje-Andreassen, Ulrike; Cramariuc, Dana; Sindre, Rasmus Bach; Pirinen, Jani; Suihko, Satu; Sarkanen, Tomi; Virtanen, Marko; Ryodi, Essi; Jakala, Pekka; Hedman, Marja; et al. (Springer Science and Business Media LLC, 2026)
Introduction: Cardiac organ damage (OD) is associated with increased risk of cardiovascular disease. However, limited knowledge exists on cardiac OD in young patients with cryptogenic ischaemic stroke (CIS).
Aim: To explore prevalence and covariates of cardiac OD in patients with CIS compared to controls participating in the SECRETO study.
Methods: We analysed data from 427 patients with CIS aged <50 years and 361 age- and sex-matched controls. OD was defined as presence of abnormal left ventricular (LV) geometry (LV hypertrophy or concentric remodelling) or left atrial enlargement (LAE) assessed by echocardiography, using sex-specific threshold values.
Results: Compared to controls, patients had higher prevalences of obesity and tobacco smoking, patent foramen ovale (PFO) (52% vs. 25%) and abnormal LV geometry (12% vs. 7%, all p < 0.01), while presence of LAE did not differ. In multivariable analyses, CIS was associated with presence of abnormal LV geometry (odds ratio 1.86 [95% confidence interval 1.09-3.20], p=0.024). In separate multivariable analyses in patients only, obesity was associated with both abnormal LV geometry and LAE (both p < 0.01), and higher systolic blood pressure only with presence of abnormal LV geometry (p < 0.001). No significant association with PFO was found.
Conclusion: In young patients with CIS participating in the SECRETO study, abnormal LV geometry was more prevalent compared to age- and sex-matched controls and associated with presence of higher blood pressure and obesity. The results point to the importance of blood pressure and weight control in CIS to prevent progression of cardiac OD and recurrent cardiovascular events.